The Growth Rate Distribution of Firms: A Dynamic Model - Kaldasch, Joachim (International Journal of Economics and Financial Issues, 2025)
The paper introduces a dynamic model for firm growth, demonstrating that Gibrat’s law is associated with a Laplace distribution of growth rates. By considering the relationship between size and growth rate, the analytical model predicts heavier tails than those observed in the Laplace distribution, indicating that Gibrat’s law is not generally applicable. The theory is validated through an analysis of companies in the pharmaceutical sector, showing strong alignment with empirical data without the need for free parameters.